2016
DOI: 10.7324/japs.2016.60910
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of lamivudine sustained release tablet using okra mucilage

Abstract: The present study was to extract the mucilage from the Okra plant (Abelmoschus esculentus) and to study the effect of mucilage concentration on in vitro release of Lamivudine from it's sustained release matrix tablets. Mucilage was extracted from the fruits of Abelmoschus esclentus using organic solvent Acetone. The extracted mucilage was subjected to various physiological properties for its suitability as an excipient in the preparation of tablet. Lamivudine sustained release tablets were prepared using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The results of the current study show great compatibility with the results of a study performed in the past, that is, mucilage showed good solubility in warm water as compared to cold water, and is completely insoluble in organic solvents (Farooq et al, 2013). Moreover, 1% okra mucilage has a viscosity of 240 cP and was well compatible with previous findings of Palei et al (2016), which reported okra mucilage viscosity of 247.34 cP.…”
Section: Solubility and Viscosity For The Extracted Okra Mucilagesupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the current study show great compatibility with the results of a study performed in the past, that is, mucilage showed good solubility in warm water as compared to cold water, and is completely insoluble in organic solvents (Farooq et al, 2013). Moreover, 1% okra mucilage has a viscosity of 240 cP and was well compatible with previous findings of Palei et al (2016), which reported okra mucilage viscosity of 247.34 cP.…”
Section: Solubility and Viscosity For The Extracted Okra Mucilagesupporting
confidence: 92%
“…Moreover, 1% okra mucilage has a viscosity of 240 cP and was well compatible with previous findings of Palei et al . (2016), which reported okra mucilage viscosity of 247.34 cP.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 5, the larger band in the region of 3600-3100 cm -1 with a sharp peak centered at 3271 cm -1 is characteristic O-H stretching vibration and hydrogen bond of the hydroxyl groups [17]. These groups serve as active sites for the attachment of colloidal particles and okra powder [2].…”
Section: Resultsmentioning
confidence: 99%
“…Palei, Mamidi, and Rajangam [ 98 ] prepared lamivudine controlled release tablets using different concentrations of okra mucilage as an excipient and observed that the in vitro release decreased with the increasing mucilage concentration, thus confirming its ability to control the release of lamivudine from the matrix. Table 2 shows other applications of okra mucilage as an excipient in pharmaceutical preparations.…”
Section: Pharmaceutical Technologymentioning
confidence: 99%